Regulation of ornithine decarboxylase gene expression by the Wilms' tumor suppressor WT1. - Moshier, J A (1996)
The importance of ornithine decarboxylase (ODC) to cell proliferation is underscored by the complex array of cell-specific mechanisms invoked to regulate its synthesis and activity. Misregulation of ODC has severe negative consequences on normal cell function, including the acquisition of tumorigenic growth properties by cells overexpressing ODC. We hypothesize that ODC gene expression is a candidate target for the anti-proliferative function of certain tumor suppressors. Here we show that the Wilms' tumor suppressor WT1 binds to multiple sites within the human ODC promoter, as determined by DNase I protection and methylation interference assays. The expression of WT1 in transfected HCT 116, NIH/3T3 and HepG2 cells represses activity of the ODC promoter controlling expression of a luciferase reporter gene. In contrast WT1 expression enhances ODC promoter activity in SV40-transfected HepG2 cells. Both the extent of modulation of ODC gene expression and the mediating WT1 binding elements are cell specific. Constructs expressing WT1 deletion mutants implicate two regions required for repressor function, as well as an intrinsic activation domain. Understanding the regulation of ODC gene expression by WT1 may provide valuable insights into the roles of both WT1 and ODC in development and tumorigenesis.